Menelaah Konsep Human Security: Studi Kasus Penanganan Masalah Pengungsi Afganistan di Australia (1999-2002) - Azis, Avyanthi (UI Scholars Hub, 2004)
This article is a short report drawn from a research on the issue of the Afghan refugees in Australia (1992-2002). Using the infamous “boat people” case as illustration, the research was intended to provide careful observation on the concept “human security,” a term increasingly linked to forced migration issues. Although human security is often portrayed as a benign concept with strong moral stance, its vastness and loose definition limit its adequacy as a useful tool of analysis. The concept is also prone to misuse because it loosely adapts to various ideological interests. Following a framework elaborated from the thoughts of Caballero-Anthony and Freitas, the article shows that it is possible to implement the human security approach in two conflicting dimensions, positive (the ideal) or negative. Both serve to protect the individuals, but each secures a different entity.